Fractal Analysis of the Academic Performance of College Students (Asia Pacific Journal of Social and Behavioral Sciences, 2013)
This paper investigated the fractal characteristics of the academic performance of college students. Final grades of the students in Mathematics, English, Science and Filipino were used to measure their academic performance. Fractal dimensions were obtained, and the self-similarity of the academic performance of students across colleges was investigated using fractal spectrum. Results revealed that the academic performance of students is fractal in nature but bounded. Self-similarity is also found in students’ academic performance in the four subjects mentioned across colleges. With this finding, implications to educators to understand and improve academic performance of students can be addressed.
Keywords: Fractal analysis, students’, performance, spectrum, ruggedness